2010
DOI: 10.1016/j.dam.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A new approximation algorithm for the multilevel facility location problem

Abstract: a b s t r a c tIn this paper we propose a new integer programming formulation for the multilevel facility location problem and a novel 3-approximation algorithm based on LP-rounding. The linear program that we use has a polynomial number of variables and constraints, thus being more efficient than the one commonly used in the approximation algorithms for these types of problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Erlenkotter [12] and Guignard [18] proposed dual-ascent algorithms for the uncapacitated facility location problem. A number of studies have applied dualascent approaches to adaptations of the uncapacitated facility location problem [7], including the multi-echelon variation [16,23,40], the location problem with a balancing requirement [3,9,36], and a multilevel version [6,14,37]. Furthermore, Guignard and Opaswongkarn [19] proposed a dual-ascent approach to the capacitated facility location problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Erlenkotter [12] and Guignard [18] proposed dual-ascent algorithms for the uncapacitated facility location problem. A number of studies have applied dualascent approaches to adaptations of the uncapacitated facility location problem [7], including the multi-echelon variation [16,23,40], the location problem with a balancing requirement [3,9,36], and a multilevel version [6,14,37]. Furthermore, Guignard and Opaswongkarn [19] proposed a dual-ascent approach to the capacitated facility location problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2], in which, however, it is shown that the reformulation applied to both levels yields to out-of-memory problems due to the large number of binary variables introduced and is, therefore, unsuitable for general purpose solvers. A comparison between the compact model IP strengthened by inequalities (8) and (9) and the discretized model DU-IP including (15) and (16) is reported in Section 4.…”
Section: Reformulation By Discretization Of the Upper Level Location mentioning
confidence: 99%
“…Each client must be assigned to a path of k facilities, and its demand must be routed through a facility of each level following a given order. Classical heuristics and exact approaches have been presented in [30]; recent approaches to the problem include approximation algorithms [15], metaheuristics [25], and polyhedral studies [24]. However, unlike the case we consider in this article, neither capacity nor single source restrictions are imposed: each facility can be fractionally assigned to many upper level facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Aardal et al [2] propose some facet defining and valid inequalities for the polytope associated with the two level uncapacitated facility location problem. Approximation algorithms are studied by Aardal et al [1], Ageev [3], Ageev et al [4], Bumb [9], Bumb and Kern [10], Gabor and van Ommeren [14], Guha et al [16], Meyerson et al [22], Shmoys et al [26], Zhang [32], and Zhang and Ye [33]. Branch and bound algorithms are given by Kaufman et al [18], Ro and Tcha [25], Tcha and Lee [29], and Tragantalerngsak et al [31].…”
Section: Introductionmentioning
confidence: 99%